Missing girls: low child sex ratio, study from urban slum and elite area of Nagpur (Health Renaissance, 2011)
Objectives: To find the child sex ratio in the urban slum and elite area of Nagpur and also to compare child sex ratio according to birth order and sex of previous born child. Methods: The study involved house to house interview of mothers of 0-6 years children from urban slum and elite area of Nagpur city. Information regarding all children born in last 6 years, their date of birth, birth order, sex, interval between two births and information regarding any abortions were noted. Results: Child sex ratio was 934 females per 1000 males combined for both areas. Child sex ratio was significantly low (P